Activation of microhelix charging by localized helix destabilization - Alexander, Rebecca W. (The National Academy of Sciences, 1998)
We report that aminoacylation of minimal RNA helical substrates is enhanced by mismatched or unpaired nucleotides at the first position in the helix. Previously, we demonstrated that the class I methionyl-tRNA synthetase aminoacylates RNA microhelices based on the acceptor stem of initiator and elongator tRNAs with greatly reduced efficiency relative to full-length tRNA substrates. The cocrystal structure of the class I glutaminyl-tRNA synthetase with tRNA(Gln) revealed an uncoupling of the first (1⋅72) base pair of tRNA(Gln), and tRNA(Met) was proposed by others to have a similar base-pair uncoupling when bound to methionyl-tRNA synthetase. Because the anticodon is important for efficient charging of methionine tRNA, we thought that 1⋅72 distortion is probably effected by the synthetase–anticodon interaction. Small RNA substrates (minihelices, microhelices, and duplexes) are devoid of the anticodon triplet and may, therefore, be inefficiently aminoacylated because of a lack of anticodon-triggered acceptor stem distortion. To test this hypothesis, we constructed microhelices that vary in their ability to form a 1⋅72 base pair. The results of kinetic assays show that microhelix aminoacylation is activated by destabilization of this terminal base pair. The largest effect is seen when one of the two nucleotides of the pair is completely deleted. Activation of aminoacylation is also seen with the analogous deletion in a minihelix substrate for the closely related isoleucine enzyme. Thus, for at least the methionine and isoleucine systems, a built-in helix destabilization compensates in part for the lack of presumptive anticodon-induced acceptor stem distortion.